2011
DOI: 10.1101/cshperspect.a005090
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis

Abstract: Extracellular matrix (ECM) is essential for all stages of angiogenesis. In the adult, angiogenesis begins with endothelial cell (EC) activation, degradation of vascular basement membrane, and vascular sprouting within interstitial matrix. During this sprouting phase, ECM binding to integrins provides critical signaling support for EC proliferation, survival, and migration. ECM also signals the EC cytoskeleton to initiate blood vessel morphogenesis. Dynamic remodeling of ECM, particularly by membrane-type matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
310
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(314 citation statements)
references
References 112 publications
2
310
0
2
Order By: Relevance
“…As described above, the lumens that were observed in our study were relatively homogenous in size, being formed from either single cells or pairs of cells with the size distribution between 50 and 200 ÎŒm 2 , as was described in earlier studies. 3,25,28 It was also shown earlier that these lumens are formed from intracellular vacuoles that subsequently coalesce to form intracellular lumens, which then merge further to form multicellular capillary tubes. 3,25,28 In contrast, blood vessels that were observed by Critser et al 27 in collagen plugs in vivo were highly variable, ranging from small vessels to large multicellular structures of up to 4,000 ÎŒm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described above, the lumens that were observed in our study were relatively homogenous in size, being formed from either single cells or pairs of cells with the size distribution between 50 and 200 ÎŒm 2 , as was described in earlier studies. 3,25,28 It was also shown earlier that these lumens are formed from intracellular vacuoles that subsequently coalesce to form intracellular lumens, which then merge further to form multicellular capillary tubes. 3,25,28 In contrast, blood vessels that were observed by Critser et al 27 in collagen plugs in vivo were highly variable, ranging from small vessels to large multicellular structures of up to 4,000 ÎŒm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…3,25,28 It was also shown earlier that these lumens are formed from intracellular vacuoles that subsequently coalesce to form intracellular lumens, which then merge further to form multicellular capillary tubes. 3,25,28 In contrast, blood vessels that were observed by Critser et al 27 in collagen plugs in vivo were highly variable, ranging from small vessels to large multicellular structures of up to 4,000 ÎŒm 2 . We suggest, therefore, that an increase in collagen has a differential effect on the formation of single-cell capillaries observed in our study versus multicellular structures observed previously in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to glial scar formation, the migration of pericytes is critically involved in the angiogenesis process (35), where pericytes are recruited to endothelial cell-lined tubes along the ablumenal surface to facilitate vessel maturation by inducing vascular basement membrane matrix deposition (36). Because angiogenesis is essential during development and organ repair, the imbalance in the angiogenesis process contributes to numerous human disorders, including cancer, diabetes, infection, and ischemic diseases (37).…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the tissue also initiates angiogenesis (formation of new blood vessels from pre-existing blood vessels). 12 Wound angiogenesis is tightly associated with granulation tissue formation and has many similarities to re-epithelialization. Similarly to the epithelial cells, the endothelial cells or their precursor cells in the pre-existing blood vessels become activated by cytokines and start to migrate to the wound provisional matrix.…”
Section: Overviewmentioning
confidence: 99%